Disaster anxiety and self-assistance behaviours among persons with cervical cord injury in Japan: a qualitative study. Issue 4 (18th April 2016) - Takahashi, Kyo; Kitamura, Yayoi
Abstract : Objectives: Persons with disabilities, especially those with a severe disability, have a vague anxiety about future disasters; however, the measures of self-assistance for disaster preparedness have not been standardised. The present study aimed to describe disaster-related anxiety and behaviours related to disaster preparedness among persons who have cervical cord injury in Japan. Design: Qualitative study. Setting: Tokyo Metropolitan area, Japan. Participants: 16 persons with cervical cord injury participated. Inclusion criteria were being 20 years old and older, being diagnosed with cervical cord injury, being able to communicate verbally, having an interest in disaster preparedness, and belonging to a self-help group of persons with cervical cord injury in the Tokyo Metropolitan area. Results: Participants usually had 'anxiety about health management' and it became more serious once they thought about a disaster. We identified three themes in relation to their anxiety: 'storing needed items, ' 'staying in a safe place' and 'having reliable caregivers.' We also identified three other themes that were the reasons behind these themes: 'travel experiences, ' 'experiences of failure' and 'information from peers.' Conclusions: To buffer the anxiety about health management in a disaster, it would be important for persons with cervical cord injury to store needed items, stay in a safe place and have reliable caregivers. Various daily experiences, including experiences of failure, would encourage such behaviours.